2022
DOI: 10.1055/s-0041-1742135
|View full text |Cite
|
Sign up to set email alerts
|

Contiguous-Level Unilateral Cervical Spine Facet Dislocation—A Report of a Less Discussed Subtype

Abstract: Unilateral facet dislocation of subaxial cervical spine trauma is characterized by dislocation of inferior facet of superior vertebra over the superior facet of inferior vertebra. The injury is due to high-velocity trauma and associated with instability of spinal column. Such unilateral facet dislocations occurring at multiple adjacent levels for some reason are not reported or studied frequently. We have reported two cases of multiple-level dislocation of unilateral facets managed in our hospital with a revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…16 Combined anterior and posterior approaches offer greatest biomechanical stability 16,21,22 and are particularly suitable if there is extensive ligamentous damage (as seen in bilateral facet dislocations) or when accompanied by corpectomies for vertebral body fractures 21,22 as happened in these cases too. 3 The take-home points from this study 3 would thus be:…”
Section: Is There Any Preferred Surgical Approach (Either Anterior Or...mentioning
confidence: 99%
See 3 more Smart Citations
“…16 Combined anterior and posterior approaches offer greatest biomechanical stability 16,21,22 and are particularly suitable if there is extensive ligamentous damage (as seen in bilateral facet dislocations) or when accompanied by corpectomies for vertebral body fractures 21,22 as happened in these cases too. 3 The take-home points from this study 3 would thus be:…”
Section: Is There Any Preferred Surgical Approach (Either Anterior Or...mentioning
confidence: 99%
“…The corollary we can draw from this is that not only is operative intervention mandatory in UFD, one must also look carefully for signs of covert adjacent segment injury like undisplaced facet fractures (which may be a milder form of the contiguous UFD described by Das et al 3 ) and if found would mandate inclusion of more levels in the fixation.…”
Section: Is There a Role For Conservative Treatment (Only Closed Redu...mentioning
confidence: 99%
See 2 more Smart Citations